The Position and Shifts of Work Values in the Context of Different Generations in Lithuania - Mažeikaitė, Daiva; Gruževskis, Boguslavas (Socialinė teorija, empirija, politika ir praktika, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian] Work values are considered to be fundamental due to the peculiar impact of work on human life and the functioning of society. The realization of them largely determines the person’s position in society and the opportunities for his career, the potential of the human and economic capital of the country, the efficiency of the use of human resources in separate companies etc. There were found significant differences between cohorts of different generations in terms of work values. The concept of “generation” could be perceived in different aspects, in this paper it is used according to understanding of Mannheim, Steel and Taras, and Strauss and Howe. Generations of Veterans, Baby Boom, X, Y and Z were distinguished. Analysis of the changes in the work values of the Lithuanian population in the aspect of generational change in the turn of the XX - XXI centuries is based on the data of the second (1990), third (1999) and fourth (2008) waves of European values survey (EVS). The research has shown that the change of generations and their individual characteristics has the greatest impact on the change of emotional work-related values, while cognitive and instrumental work-related values are influenced by changes in the socioeconomic context.